2020
DOI: 10.1038/s41598-020-60732-w
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive detection of saccharides using terahertz sensor based on metallic nano-slits

Abstract: Unambiguous identification of trace amounts of biochemical molecules in a complex background using terahertz spectroscopy is extremely challenging owing to the extremely small absorption cross sections of these molecules in the terahertz regime. Herein, we numerically propose a terahertz nonresonant nano-slits structure that serves as a powerful sensor. The structure exhibits strongly enhanced electric field in the slits (five orders of magnitude), as well as high transmittance over an extra-wide frequency ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This granularity in design ensures that gas molecules can be selectively separated with a high degree of precision. Selective adsorption by organic cages has been demonstrated for a number of gas pairs including CO 2 /CH 4 , 19,141,142 CO 2 /N 2 , [142][143][144] Xe/Kr, 115,145 and H 2 /D 2 . 146 Removing CO 2 from the atmosphere or other gases may be one of the last viable ways to mitigate catastrophic climate change.…”
Section: Gas Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…This granularity in design ensures that gas molecules can be selectively separated with a high degree of precision. Selective adsorption by organic cages has been demonstrated for a number of gas pairs including CO 2 /CH 4 , 19,141,142 CO 2 /N 2 , [142][143][144] Xe/Kr, 115,145 and H 2 /D 2 . 146 Removing CO 2 from the atmosphere or other gases may be one of the last viable ways to mitigate catastrophic climate change.…”
Section: Gas Separationmentioning
confidence: 99%
“…Many studies have reported the ideal selectivity in gas pairs of CO 2 /N 2 or CO 2 /CH 4 achieved by POCs. 19,[141][142][143][144] The size of the cage interior in POCs is tailored by selecting appropriate precursors and employing post-synthetic modification strategies, consequently facilitating selective adsorption by precisely differentiating the size among various gas molecules. Also, the introduction of specific functional groups into the cage structure can enhance its capacity for CO 2 adsorption.…”
Section: Gas Separationmentioning
confidence: 99%
“…Therefore, a large quantity of samples is needed to observe significant fingerprint absorption signals [8][9][10][11]. In the past few years, to enhance the detection sensitivity and achieve the identification of trace analytes, metasurface structures have been introduced, such as metal gratings, split-ring resonators, dielectric metasurfaces, nano-antenna arrays, and waveguide structures [12][13][14][15][16][17][18][19][20][21]. These additional structures aim to amplify the electromagnetic interaction between the electromagnetic waves and analyte samples, thereby magnifying the fingerprint absorption of the analytes.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, researchers have proposed various artificially designed metasurface structures, including open-ring resonators [11], metal gratings [12], photonic crystal structures [13], waveguide configurations [14], and structures based on bound states in the continuum [15,16], to achieve heightened sensitivity in material detection [17][18][19]. The majority of these structures are limited to detecting material absorption characteristics at individual frequency points via resonance peaks.…”
Section: Introductionmentioning
confidence: 99%